Effect of potassium and zinc on growth, yield and quality of garlic (Allium sativum L.) (Indian Journal of Arid Horticulture, 2018)
Afield experiment was conducted during Rabiseason 2017-18 at the Research Farm, College of Horticulture, Mandsaur  (M.P.) to study the response of potassium and zinc on growth, yield and quality of garlic. The experiment was laid out in factorial  RBD design with three replications including four levels of potassium (0, 25, 50 and 75 kg K O/ha) and three levels of zinc (0, 5 2 and 10 kg Zn/ha). Results showed that application of K Z (75 Kg K O/ha + 10 Kg Zn/ha) significantly increased the plant height, 3 2 2 number of leaves per plant, fresh weight of plant (g), dry weight of plant (g) fresh weight of bulb (32.4g), dry weight of bulb (10.22  g), polar diameter of bulb (4.73 cm), equatorial diameter of bulb (4.72 cm), bulb yield (146.7 q/ha), volatile oil content in bulb  (0.40%) and non-significant effect showed in TSS content in bulb (42.51 Brix). Therefore, the application of 75 Kg K O/ha and 2  10 Kg Zn/ha gave maximum growth, yield and quality attributes and of garlic.
Keywords: Garlic; potassium; zinc; growth; volatile oil